Effect of Phenylalanine–Arginine Beta-Naphthylamide on the Values of Minimum Inhibitory Concentration of Quinolones and Aminoglycosides in Clinical Isolates of Acinetobacter baumannii - Plasencia-Rebata, Stefany (2023)
Background: Acinetobacter baumannii has become the most important pathogen responsible for nosocomial infections in health systems. It expresses several resistance mechanisms, including the production of β-lactamases, changes in the cell membrane, and the expression of efflux pumps. (2) Methods: A. baumannii was detected by PCR amplification of the blaOXA-51-like gene. Antimicrobial susceptibility to fluoroquinolones and aminoglycosides was assessed using the broth microdilution technique according to 2018 CLSI guidelines. Efflux pump system activity was assessed by the addition of a phenylalanine–arginine beta-naphthylamide (PAβN) inhibitor. (3) Results: A total of nineteen A. baumannii clinical isolates were included in the study. In an overall analysis, in the presence of PAβN, amikacin susceptibility rates changed from 84.2% to 100%; regarding tobramycin, they changed from 68.4% to 84.2%; for nalidixic acid, they changed from 73.7% to 79.0%; as per ciprofloxacin, they changed from 68.4% to 73.7%; and, for levofloxacin, they stayed as 79.0% in both groups. (4) Conclusions: The addition of PAβN demonstrated a decrease in the rates of resistance to antimicrobials from the family of quinolones and aminoglycosides. Efflux pumps play an important role in the emergence of multidrug-resistant A. baumannii strains, and their inhibition may be useful as adjunctive therapy against this pathogen.